Manajemen Dan Kepemimpinan Dalam Lembaga Pendidikan Islam - Miswanto (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Management of Islamic education is a process of managing Islamic educational institutions in the Islamic way by getting around the sources of learning and other matters related to achieving the objectives of Islamic education effectively and efficiently. The function of Islamic education management includes; Planning, organizing, directing / leadership, and supervision. Where as a Manager must be able to carry out, manage the process of management functions which include (1) planning, (2) coordination / organization, (3) direction, (4) control / supervision and (5) evaluation / assessment. Leadership is an effort someone in influencing others to do something for the sake of the realization of desires or goals that have been set together consist of : the existence of a group of people, the goals to be achieved, working together. Islamic education is the formation of the character of children to become human beings who have a morality so that in everyday life they get happiness, peace, and can reflect behavior in accordance with Islamic ways which is based on the Qur'an, Sunnah  and Ijtihad